Ecological health assessment of a coastal ecosystem: Case study of the largest brackish water lagoon of Asia. (January 2019) - Barik, Saroja Kumar; Bramha, Satyanarayan; Behera, Dibakar; Bastia, Tapan Kumar; Cooper, Gregory; Rath, Prasanta
Abstract: This study focuses on the ecological health assessment of Chilika, a shallow lagoon present in east coast of India, through nutrient stoichiometry and trophic state index (TSI). Multivariate statistical analysis such as ANOVA, Pearson's correlation, Principal Component Analysis (PCA), and Discriminant Analysis (DA) were employed for data interpretation. Nutrient stoichiometry revealed that the Chilika Lagoon experiences phosphorus limitation with regard to nitrogen and silicate (N:P:Si = 16:1:16) throughout the study period. As per the computed TSI values, the southern sector (SS), central sector (CS), and outer channel (OC) were assigned with a mesotrophic status, whereas the northern sector (NS) was assigned with the eutrophic status. From PCA, total nitrogen was found to be negatively correlated with salinity and positively correlated with silicate, thus indicating that the major source of nitrogen in the lagoon was freshwater ingress by rivers with high silicate content. DA indicated that it was successful in discriminating the groups as predicted. Highlights: Trophic state index (TSI) and nutrient stoichiometry ratio are used to access ecological health of Lake System. Contour maps shows the spatial distributions of water quality parameters in Chilika lake and drawn by Surfer software. High canonical correlation indicates a significant relation between group of variables and functions of discriminate. With respect to trophic state index, northern sector of Chilika lagoon categorized as eutrophication zone. The findings may be the baseline reference for the lake scientist to find out the source of nutrient load to the sectors.